THE EFFECTS OF THE PRESENCE OF UiTM NEGERI SEMBILAN BRANCH CAMPUSES ON BUSINESSES IN KUALA PILAH, SEREMBAN AND REMBAU - A. N. Jannah; A. Shanthi (Journal of Academia)
UiTM Negeri Sembilan Branch started off as a temporary campus and began operating on 1 June 1999. Today after more than 20 years, this branch has expanded and currently operates with three permanent campuses in Kuala Pilah, Seremban and Rembau. The current study on the 20-year-Impact of UiTM Negeri Sembilan Branch focusses on identifying the impact of the existence of UiTM Negeri Sembilan Branch on the development and progress it has brought upon the people and surrounding areas of the three campuses. The impact of the establishment of UiTM Negeri Sembilan Branch can be seen not only through the growth it has brought to the human resources, academic and physical sectors, but can also be seen via the impact it has brought to the economic, political, social as well as the environment sectors on the communities of Kuala Pilah, Seremban, and Rembau. This paper aims to show the impact by focusing on the industry or businesses that exist around UiTM Negeri Sembilan Branch. Data for the study was collected through questionnaires and interviews with respondents. The feedbacks were received from 63 respondents (industry/business) operating around Kuala Pilah, Seremban, and Rembau. Through the analysis of this study, detailed and in-depth information on industries/businesses around the campus is collected and used as a reference for the planned follow-up study. This study can be used as a reference source for UiTM to formulate various strategies, programs, and value-added activities that could improve the quality of life and well-being